The Influence of Taxation Knowledge, Tax Officer Services, and Implementation of E-Filing on Taxpayer Compliance With Tax Sanctions as a Moderation Variable (Empirical Study on Individual Taxpayers at Kpp Pratama Jakarta Gambir Satu in 2023) - Anoraga, Adhi; Muslim, Sabarudin (Universitas Mercu Buana, 2024)
This study aims to determine the effect of tax knowledge, tax officer services, and the application of e-filing on taxpayer compliance with tax sanctions as a moderating variable. This study employs the purposive sampling method, calculating the sample size using the Slovin formula. The data used in this study is primary and cross-sectional data originating from distributing questionnaires to 100 individual taxpayers at KPP Pratama Jakarta Gambir Satu in 2023. The data analysis method used is multiple linear regression analysis, consisting of three main variables (independent, dependent, and moderating variables). The independent variables consist of knowledge of taxation, tax officer services, and the application of e-filing; the dependent variable is taxpayer compliance; and the moderating variable is tax sanctions. This type of research uses a causal study approach to test whether one variable causes other variables to change or not. The design of this research employs a quantitative descriptive study approach to gather useful data that can explain the characteristics of one variable in relation to other variables. The tool used to test this research is the SPSS version 26 application. The results of this study indicate that knowledge of taxation, tax officer services, and the application of e-filing have no effect on taxpayer compliance, while tax sanctions as a moderating variable cannot affect the relationship between tax knowledge, tax officer services, and the application of e-filing to individual taxpayer compliance.